Problems arising when teaching English in the humanities - Urazkulova, Aziza (The Lingua Spectrum, 2025)
In the modern education system, language learning is not limited to mastering grammar and lexical rules. In the current era of globalization, English is not only the language of international communication, but also plays an important role in humanitarian fields. When students in the humanities are studying in fields such as literature, sociology, psychology, and cultural studies, mastering the English language is important for expanding their knowledge and skills, conducting scientific research, and establishing international relations. However, there are a number of problems in teaching English to humanities students. Among these problems, lack of special vocabulary, lack of contextual knowledge, lack of development of communication skills and motivation issues require special attention. Without solving these problems, students will not be able to learn English correctly and effectively. The purpose of this project work is to identify problems in the process of English language teaching for humanitarian students and suggest ways to overcome them. Approaches such as innovative educational methods, interactive training and intercultural communication are considered to overcome the problems. In turn, improving the English language teaching process opens up new opportunities for humanitarian students and helps their professional development.